Oxidation and Reduction of Iron-Titanium Oxides in Chemical Looping Combustion: A Phase-Chemical Description Oxydation et réduction des minerais de fer-titane dans la combustion en boucle chimique - den Hoed P.; Luckos A. (Oil & Gas Science and Technology, 2011)
Ilmenite (FeTiO3) is being explored as an oxygen carrier in chemical looping processes. Its reduction and oxidation are described by the system Fe-Fe2O3-TiO2-Ti2O3. The phase diagram at 1 000°C, presented here, offers a useful tool for predicting reactions and their products. We see that Fe2TiO5 (pseudobrookite) and TiO2 (rutile) form a stable phase assemblage following the oxidation of FeTiO3 (ilmenite) in air. The subsequent reduction of Fe2TiO5 at oxygen partial pressures of 10-15.5atm stabilizes Fe1.02Ti0.98O3, a solid solution of ilmenite. Further reduction will produce metallic iron, which compromises the integrity of the oxygen carrier for chemical looping processes. We speculate that the reduction of Fe-Ti oxides in several practical instances does not reach completion (and equilibrium) under the imposed atmospheres operating in fuel reactors. L’ilménite (FeTiO3) est considéré comme un transporteur d’oxygène potentiel pour les procédés en boucle chimique. Ses mécanismes de réduction et d’oxydation sont décrits à travers le système Fe-Fe2O3-TiO2-TiO3. Le diagramme de phase à 1 000°C, présenté ici, est un outil utile pour prédire les réactions et les produits. Nous constatons que Fe2TiO5 (pseudobrookite) et TiO2 (rutile) forment un assemblage de phase stable après oxydation de l’ilménite (FeTiO3) dans l’air. La réduction subséquente de Fe2TiO5 à la pression partielle de 10−15,5atm stabilise vers Fe1.02Ti0.98O3, une solution solide d’ilménite. Une réduction plus poussée va produire du fer métallique et compromettre l’intégrité du transporteur d’oxygène dans la boucle chimique. Il est probable que la réduction des oxydes Fe-Ti ne soit pas, en pratique, complète et n’atteigne pas l’équilibre dans les conditions rencontrées en opération dans les réacteurs de réduction.